Metastatic Tumor of the Spermatic Cord in Adults: A Case Report and Review - Daisaku Hirano; Mizuho Ohkawa; Ryo Hasegawa; Norimichi Okada; Naoki Ishizuka; Yoshiaki Kusumi (Case Reports in Urology)
Metastatic spermatic cord (SC) tumor is extremely rare. Recently, we experienced a case of late-onset metastatic SC tumor from cecal cancer. This case is a 68-year-old man presenting with a painless right SC mass. He had undergone a right hemicolectomy for cecal cancer 6 years ago. Radical orchiectomy and adjuvant chemotherapy with S-1 were performed. No recurrence was found after one year of follow-up. We identified a total of 25 cases, including our case, on a literature search via PubMed from January 2000 to April 2015. The most frequent primary sites of the tumors metastasizing to the SC were the stomach (8 cases, 32%) and the colon (8 cases, 32%), next the liver (2 cases, 8%), and kidney (2 cases, 8%). The majority of the cases underwent radical orchiectomy for the metastatic tumors of the SC. Over half of the cases received adjuvant interventions based on the regimens for the primary tumors. Prognosis in the patients with metastatic tumor of the SC was unfavorable except for late-onset metastasis. In patients with a mass in the SC and a history of neoplasm, especially in gastrointestinal tract, the possibility of metastasis from the primary cancer should be considered.